Research of elasto-plastic bending of thin shells and plates by the R-fanctions method - Morachkovska, Irina; Timchenko, Galina; Lyubitska, Kateryna (NTU "KhPI", 2016)
The effective method basing on theory of R-functions and variational structural method is developed for solving non-linear boundary problems. Elastic-plastic bending of thin shallow shells is considered. The problems are reduced to finding stationary points of suggested mixed variational functionals according to the initial linearization due to usage of subsequent loading and Newton-Kantorovich jointly with method of varying elastic parameters. The method is used for automatic calculations in "POLE" programming system for investigations of shell structural elements. The numerical justification of the method is given. New laws of non-linear deformation of shallow shells and plates with complex shapes in plane are established.

Розглядається ефективний метод розв'язання нелінійних крайових задач пружно-пластичного згину тонких пологих оболонок, який базується на теорії R-функцій. Задача зводиться до знаходження точок стаціонарності запропонованих змішаних варіаційних функціоналів, лінеаризованих за схемою методу послідовних навантажень Ньютона-Канторовича спільно з методом змінних параметрів пружності. Чисельні дослідження виконані з використанням програмуючої системи "ПОЛЕ". Встановлено нові закони нелінійного деформування пологих оболонок і пластин складної форми в плані.
Дослідження пружно-пластичного згину тонких оболонок і пластин методом R-функцій
Keywords: shallow shells; elasto-plastic deformations; R-functions theory; тонкі пологі оболонки; пружно-пластичні деформації; теорія R-функцій; послідовні навантаження; параметри пружності; нелінійне деформування